Oral Dexmedetomidine Promotes Non-rapid Eye Movement Stage 2 Sleep in Humans - Chamadia, Shubham (Anesthesiology, 2020)
BACKGROUND: The administration of dexmedetomidine is limited to highly monitored care settings because it is only available for use in humans as an intravenous medication. An oral formulation of dexmedetomidine may broaden its use to all care settings. Therefore, we investigated the effect of a capsule-based solid oral dosage formulation of dexmedetomidine on sleep polysomnography. METHODS: We performed a single-site, placebo-controlled randomized, cross-over, double-blind phase II study of a solid oral dosage formulation of dexmedetomidine (700mcg, n = 15). Our primary outcome was polysomnography sleep quality. Secondary outcomes included performance on the motor sequence task and psychomotor vigilance task administered to each subject at night and in the morning to assess motor memory consolidation and psychomotor function, respectively. Sleep questionnaires were also administered. RESULTS: Oral dexmedetomidine increased the duration of non-rapid eye movement (non-REM) stage 2 sleep by 63 [95% CI: 19, 107] minutes (p = 0.010) and decreased the duration of REM sleep by 42 [5, 78] minutes (p = 0.031). Overnight motor sequence task performance improved after placebo sleep (7.9%, p = 0.003) but not after oral dexmedetomidine-induced sleep (−0.8%, p = 0.900). In exploratory analyses, we found a positive correlation between spindle density during non-REM stage 2 sleep and improvement in the overnight test performance (Spearman’s Rho = 0.57, p = 0.028, n = 15) for placebo but not oral dexmedetomidine (Spearman’s Rho = 0.04, p = 0.899, n = 15). Group differences in overnight motor sequence task performance, psychomotor vigilance task metrics, and sleep questionnaires did not meet our threshold for statistical significance. CONCLUSIONS: These results demonstrate that the nighttime administration of a solid oral dosage formulation of dexmedetomidine is associated with increased non-REM 2 sleep and decreased REM sleep. Spindle density during dexmedetomidine sleep was not associated with overnight improvement in the motor sequence task.